Effects of the Reaction Parameters and Light Hydrothermal Aging for Catalytic Combustion of Propane over Co-Mn-Ce Catalyst - Lili Lei; Miaomiao Jin; Chenrui Cui; Kai Li; Pan Wang (Journal of Chemistry)
A composite oxides’ Co-Mn-Ce catalyst was synthesized by a coprecipitation method, and the experiment was carried out to study the effects of reaction parameters and light hydrothermal aging on propane combustion over the Co-Mn-Ce catalyst. The influence of reaction temperature, propane concentration, oxygen concentration, water vapor, and hydrothermal aging was studied during the catalytic combustion of propane. The propane conversion significantly decreased by 10% when the propane concentration increased at 300°C and then further decreased from 80% to 40% as water vapor concentration increased from 0 to 10 vol.%. In addition, water vapor also prolonged the time required to reach equilibrium. After hydrothermal treatment, the catalyst obtained the lowest oxidation capacity of propane. Furthermore, the results of in situ DRIFTs and O2 temperature programmed desorption (O2-TPD) demonstrated that there were fewer oxygen species after hydrothermal aging, and carbonates were the main intermediates formed during the catalytic oxidation of propane.